A Review of Antennas for Indoor Positioning Systems - Luis Brás; Nuno Borges Carvalho; Pedro Pinho; Lukasz Kulas; Krzysztof Nyka (International Journal of Antennas and Propagation)
This paper provides a review of antennas applied for indoor positioning or localization systems. The desired requirements of those antennas when integrated in anchor nodes (reference nodes) are discussed, according to different localization techniques and their performance. The described antennas will be subdivided into the following sections according to the nature of measurements: received signal strength (RSS), time of flight (ToF), and direction of arrival (DoA). This paper intends to provide a useful guide for antenna designers who are interested in developing suitable antennas for indoor localization systems.